Synthesis, Characterization of Biological Active Bidentate Heterocyclic Schiff Base Metal Complexes - Mane, P.S.; Salunke, S.M.; More, B.S.; Chondhekar, T.K. (Asian Journal of Chemistry, 2012)
The solid complexes of Cu(II), Ni(II), Co(II), Mn(II) and Fe(III) with Schiff base ligands derived from heterocyclic compounds 3-acetyl-6-methyl-(2H)-pyran-2,4(3H)dione (dehydroacetic acid) and o-anisidine were synthesized and characterized by elemental analysis, conductance, magnetic, thermal, UV-VIS and 1H NMR spectroscopy. The ligand field parameters have been evaluated for metal complexes which suggest an octahedral geometry for each of them. The magnetic moment and spectral data suggest the dimeric nature of Mn(II) complexes with octahedral geometry. The fungicidal activities of the ligands and their metal complexes have been screened in vitro against Aspergillus niger and the percentage inhibition of the metal complexes is found to be increased considerably than that of their corresponding ligands and the order is Cu > Ni > Fe > Mn > Co.